2017
DOI: 10.1007/s11356-017-9600-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Metabolic Footprinting (EMF) vs. half-life: a new and integrative proxy for the discrimination between control and pesticides exposed sediments in order to further characterise pesticides’ environmental impact

Abstract: Pesticides are regularly used for a variety of applications and are disseminated throughout the environment. These substances may have significant negative impacts. To date, the half-life, t, was often used to study the fate of pesticides in environmental matrices (water, soil, sediment). However, this value gives limited information. First, it does not evaluate the formation of by-products, resulting in the need for additional experiments to be performed to evaluate biodegradation and biotransformation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…9 Regardless of the concentrations, these products can present higher toxicity than the original compounds and may have a straight correlation with the increasing number of diseases, like cancer. [10][11][12][13][14] Besides pesticides, the presence of other emerging contaminants in the environment, such as industrial compounds, pharmaceuticals, personal care products and disinfection by-products, results in negative effects in living organisms due to the non-target effect and contributes to increase surface and groundwater pollution. 15,16 Recent studies have shown that the exposure of parents before a child's birth increases the risk of infant leukemia and Parkinson's disease to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…9 Regardless of the concentrations, these products can present higher toxicity than the original compounds and may have a straight correlation with the increasing number of diseases, like cancer. [10][11][12][13][14] Besides pesticides, the presence of other emerging contaminants in the environment, such as industrial compounds, pharmaceuticals, personal care products and disinfection by-products, results in negative effects in living organisms due to the non-target effect and contributes to increase surface and groundwater pollution. 15,16 Recent studies have shown that the exposure of parents before a child's birth increases the risk of infant leukemia and Parkinson's disease to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a problematic emergence of resistance to chemical pesticides in the phytopathogens [7]. Methods have been developed to evaluate the impact of pesticides on the environment, and they allowed to show that pesticide applications must be reduced to limit human health problems, environmental contamination and reduced soil fertility [79]. Simultaneously, new ways of crop production grouped under the generic term Integrated Pest Management (IPM) have been developed to control pests in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, agricultural types in Palestine are aiming to avoid low plant development and increase the production and the quality of the products. These changes help to introduce higher levels of herbicides in the agricultural ecosystem [4]. The main output of these agricultural practices is the contamination of soils and waters, which leads to degrade the soil–water–plant system and bioaccumulate herbicide residues.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several studies have been given to PQT 2+ , mainly due to the high rate of poisoning and fatalities attributed to it [4].…”
Section: Introductionmentioning
confidence: 99%